2023
DOI: 10.3389/fvets.2023.1184969
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of selenized-oligochitosan on zearalenone-induced intestinal dysfunction in piglets

Abstract: This paper assessed the positive effects of selenized-oligochitosan (SOC) on zearalenone(ZEN)-induced intestinal dysfunction in piglets. Sixty piglets were randomly divided into 4 groups. Group C was fed the basal diet as a control and Group Z was supplemented with 2 μg/g ZEN in the basal diet; Group ZS1 and ZS2 were supplemented with 0.3 or 0.5 μg/g SOC (calculated by selenium), in addition to 2 μg/g ZEN in the basal diet. After 42 days, ileal mucosal structure, digestive enzyme activities, tight junction pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Tryptophan has a certain therapeutic effect on inflammatory gastrointestinal diseases, which helps promote the host's intestinal health. Qin et al [106] studied the effect of seleno-oligochitosan on intestinal dysfunction in piglets and found that seleno-oligochitosan could increase the activity of antioxidant enzymes, such as superoxide dismutase and glutathione peroxidase, enhance the antioxidant capacity of intestinal tissue, and reduce the damage of oxidative stress. In addition, seleno-oligochitosan promotes the growth of beneficial bacteria and reduces the breeding of harmful bacteria, thereby maintaining the balance of intestinal flora and promoting intestinal health.…”
Section: Biomedical Fieldmentioning
confidence: 99%
“…Tryptophan has a certain therapeutic effect on inflammatory gastrointestinal diseases, which helps promote the host's intestinal health. Qin et al [106] studied the effect of seleno-oligochitosan on intestinal dysfunction in piglets and found that seleno-oligochitosan could increase the activity of antioxidant enzymes, such as superoxide dismutase and glutathione peroxidase, enhance the antioxidant capacity of intestinal tissue, and reduce the damage of oxidative stress. In addition, seleno-oligochitosan promotes the growth of beneficial bacteria and reduces the breeding of harmful bacteria, thereby maintaining the balance of intestinal flora and promoting intestinal health.…”
Section: Biomedical Fieldmentioning
confidence: 99%